Sleep structure and related clinical characteristics in drug-naïve Parkinson's disease with subjectively different sleep quality - Jiang, Yinyin; Chen, Yaning; Li, Dongfeng; Zhu, Sha; Gu, Ruxin; Wang, Yaxi; Zhu, Jun; Jiang, Xu; Shen, Bo; Pan, Yang; Yan, Jun; Zhang, Li (Frontiers in Neurology, 2023)
Abstract Background: Sleep disturbance is a common non-motor symptom in Parkinson’s disease (PD). Most polysomnography (PSG) studies are conducted when patients in their “on medication” state. Our study aimed to investigate changes in sleep structure in drug-naïve PD patients with poor subjective sleep quality based on polysomnography (PSG) and to explore potential correlations between sleep structure and clinical features of the disease. Methods: Forty-four drug-naïve PD patients were included. All patients completed a standardized questionnaire to obtain demographic and clinical characteristics and underwent whole-night PSG recording. Patients with PSQI scores >5.5 were considered to be poor sleepers and patients with PSQI scores <5.5 were considered to be good sleepers. Results: There were 24 (54.5%) PD patients in good sleeper group and 20 (24.5%) PD patients in poor sleeper group. We observed that poor sleepers had severer non-motor symptoms (NMS) and worse life quality. The PSG displayed that they had longer wake-up time after sleep onset (WASO) and lower sleep efficiency (SE). Correlation analysis revealed that micro-arousal index was positively associated with UPDRS-III and N1 sleep percentage was negatively associated with NMS score in good sleepers. For poor sleepers, rapid eye movement (REM) sleep percentage related negatively to Hoehn and Yahr (H&Y) stage, WASO increased with UPDRS-III, periodic limb movement index (PLMI) increased with NMS score, N2 sleep percentage related negatively to score of life quality. Conclusion: Night awakening is the main manifestation of decreased sleep quality in drug-naïve PD patients. Poor sleepers have severer non-motor symptoms and worse life quality. Additionally, the increase of nocturnal arousal events may predict progression of motor dysfunction.